Supplemental dietary oils rich in oleic acid or linoleic acid attenuate egg yolk and tissue n-3 polyunsaturated fatty acid contents in laying hens co-fed oils enriched in either stearidonic acid or α-linolenic acid. (September 2021) - Elkin, Robert G.; El-Zenary, Ahmed S.A.; Bomberger, Rebecca; Harvatine, Kevin J.
Highlights: High-OA oils attenuate egg yolk n-3 PUFA content when fed with n-3 PUFA-rich oils. A high-LA oil attenuates egg yolk n-3 PUFA content when fed with n-3 PUFA-rich oils. OA and LA may outcompete n-3 PUFA for uptake from the intestine. Future fatty acid digestibility studies need to be conducted to prove this hypothesis. Summary: We previously reported that when laying hens were fed diets supplemented with oils enriched in α-linolenic acid (ALA) and oleic acid (OA), the deposition of n-3 PUFA in egg yolk was attenuated as compared to feeding hens a diet supplemented with the ALA-rich oil alone. The present work extends those findings to another n-3 PUFA-rich oil (stearidonic acid [SDA]-enriched soybean oil) and two other high-OA oils, suggesting that the effect is not plant oil-specific. Feeding hens a supplemental linoleic acid (LA)-rich oil plus an oil rich in either SDA or ALA also attenuated egg yolk ALA and SDA contents (Experiment 1), or egg yolk and liver ALA contents (Experiment 2), respectively, as compared to feeding the SDA- or ALA-rich oils alone. Future work should focus on the lack of neutrality of OA and LA in relation to n-3 PUFA nutrition.